Ethnobotany of Coconut (Cocos nucifera) and Bayur (Pterospermum javanicum) Trees as Building Materials in Jabang Bayi Kebon Village, Serang, Banten - Indriati Dhiya Ulhaq; Fathiyah Salsabilah; Syahla Awalunnisa; Revalia Artha Mafilido; Rina Erfiyana; Desi Eka Nur Fitriana (Jurnal Biologi Tropis, 2026)
Ethnobotany of timber is a field of study that examines the relationship between humans and the use of plants as building materials. However, changes in lifestyles, particularly among the younger generation, have led to a decline in knowledge about the use of local plants as building materials. This situation raises concerns about the loss of ethnobotanical knowledge of woodworking, which has been passed down through generations. This study aims to examine the utilization of coconut (Cocos nucifera) and bayur (Pterospermum javanicum) trees as building and furniture materials by the community of Jabang Bayi Kebon Village, Serang, Banten. A qualitative descriptive method with an ethnobotanical approach was applied through field observations, semi-structured interviews, and documentation. The results show that coconut trees are mainly used for house structures such as walls, roofs, and fences, while bayur wood is utilized for furniture production by local craftsmen. The utilization of these plant species is based on local knowledge, material availability, and traditional practices passed down through generations. This study highlights the important role of local knowledge in supporting the sustainable use of plant resources.